2021
DOI: 10.1002/jcu.23118
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of ultrasound and contrast‐enhanced ultrasound in septic acute kidney injury

Abstract: Purpose This study aimed to explore the clinical value of ultrasonic Doppler examination and contrast‐enhanced ultrasound (US) in the circulation of septic acute kidney injury (AKI). Methods Patients with intensive care unit‐related infection were divided into AKI group and control groups. The AKI group was divided into three subgroups according to the serum creatinine value: stage 1, stage 2, and stage 3. Relevant parameters and blood flow of the renal artery were measured, and further contrast‐enhanced US wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…Oncology and radiology of Kazakhstan, №3 (65) 2022 The presented ultrasound results reflect the kidney size changes in AKI similar to those reported by P.Q. Liu [12]. A systematic review by S. Ninet al showed that an elevated resistance index could predict persistent AKI in critical patients [13].…”
Section: Case No 2 Patient Informationsupporting
confidence: 78%
“…Oncology and radiology of Kazakhstan, №3 (65) 2022 The presented ultrasound results reflect the kidney size changes in AKI similar to those reported by P.Q. Liu [12]. A systematic review by S. Ninet al showed that an elevated resistance index could predict persistent AKI in critical patients [13].…”
Section: Case No 2 Patient Informationsupporting
confidence: 78%
“…Inflammatory cervical lymph nodes or retroconvex thyroid nodules may also appear as radioconcentrated foci, making them prone to false positives, [28] and 99m Tc-MIBI imaging is unable to clarify the anatomical relationship between foci and surrounding tissues, whereas conventional ultrasound can clearly visualize the parathyroid glands with a maximum diameter of 3-5 mm and their blood flow distribution characteristics, and can also clearly visualize the cystic foci and the anatomical relationship with the surrounding tissues, which compensates for the deficiencies of 99m Tc-MIBI imaging. Zhang et al ( 2006) and Liu et al (2004) [29,30] indicated that the detection rate of ectopic parathyroid lesions by ultrasound combined with 99m Tc-MIBI dual time-phase imaging was significantly higher than that of any single examination method, such as ultrasound, CT and MRI. In this study, 5 patients with ETPG had a total of 21 parathyroid glands, and 99m Tc-MIBI imaging showed 14 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, MPUS has been used to predict hydronephrosis [ 19 , 20 ]. Meanwhile, some studies have predicted kidney injury using MPUS [ 21 , 22 ]. However, the diagnostic efficacy of MPUS in patients with sepsis-induced AKI remains unclear.…”
Section: Introductionmentioning
confidence: 99%